Pendekatan PDSA Untuk Perbaikan Proses pada Indikator Sasaran Keselamatan Pasien di Rumah Sakit - Elly Numa Zahroti (Universitas Airlangga, 2018)
Background: Patient safety is an indicator of hospital service quality. A hospital in Surabaya identified six indicators of patient safety goals. There are two indicators which can not achieve the standard, namely effective communication and infection risk reduction.Aims: This study aims to identify the process improvement that can be done to increase indicator performance by using PDSA cycle.Method: A descriptive observational design was used in this study with a case study and participatory approach. There were 5 subjects selected by purposive sampling. Interview and observation were used to collect data that then were analyzed descriptively. The validity of data was done by triangulation of method, source, and theory.Results: The PDSA results indicated that the cause of the poor indicators performance of both patient safety goals is the poor compliance of the health staffs in carrying out read-back procedure and hand hygiene as written in SOP. It was caused by the lack of knowledge and motivation of the health staffs in implementing the SOP.Conclusion: In conclusion, process improvement can be done by socializing read-back SOP and hand hygiene as well as supervision conducted periodically by managers. Plan stage is one step which should be improved. Commitment in implementing the improvement planning is necessary. In addition, further research on factors that influence compliance should be conducted.Keywords: patient safety, PDSA method, process improvement, quality of hospital